AKTIVITAS SEDIAAN GEL KUERSETIN TERHADAP Staphylococcus Epidermidis - Rina Apriana Herslambang; Dina Rahmawanty; Mia Fitriana (Universitas Tadulako, 2015)
Acne is the abnormality production of sebum in the sebaceous glands which are usually caused by Staphylococcus epidermidis. Staphylococcus epidermidis one of bacterial that caused acne. Quercetin have a phenolic compound that can inhibit the growth of Staphylococcus epidermidis at 0.05% w/w. The purpose of this study was to determine the minimum inhibitory concentration of quercetin gel. HPMC was used as gel base. The concentrations of quercetin that was added to gel were 0.05% w/w, 0.15% w/w, and 0.25% w/w. The antibacterial activity of the gels was determined using agar diffusion method. The results showed that the inhibition zone on the F1, F2, and F3 were 7.83 mm , 6.53 mm , 4.56 mm and the result showed that quercetin gels significantly effected the growth of Staphylococcus epidermidis (p<0,05). The minimum inhibitory concentration of quercetin gel was 0,05% w/w with inhibition zone of 7.83 mm.